2000
DOI: 10.1046/j.1524-475x.2000.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of virally transduced cells into the dermis of immunocompetent and immunodeficient (SCID) mice to determine gene expression profile and differential donor cell survival

Abstract: Cell therapy and bioengineering hold great promise as therapeutic approaches using cells and cell-derived factors to treat various pathologic or trauma-induced states. One possible application is the transplantation of cells into wounded tissue to help regulate tissue repair. Cells engineered for optimal wound healing may help to minimize scarring following surgery or to enhance the rate of healing of chronic wounds. The purpose of the current study was to determine the effect of a viral insert, the LacZ-beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The evidence that human donor cells are detected weeks after the acute inflammatory response is delineated and that the transected nerve is functionally regenerated supports the proposal for hMDSPCs as an effective cell therapy. Previous findings have indicated that, similar to other stem cells (70,71), MDSPCs display immune-privileged properties (37), including their ability to survive, divide, and participate in wound healing in a similar fashion in normal and SCID mice (72). Moreover, even though tumor formation is common after neuronal axotomy (73), we observed no sign of tumor formation at the site of injury up to 18 months after transplantation.…”
Section: Methodssupporting
confidence: 48%
“…The evidence that human donor cells are detected weeks after the acute inflammatory response is delineated and that the transected nerve is functionally regenerated supports the proposal for hMDSPCs as an effective cell therapy. Previous findings have indicated that, similar to other stem cells (70,71), MDSPCs display immune-privileged properties (37), including their ability to survive, divide, and participate in wound healing in a similar fashion in normal and SCID mice (72). Moreover, even though tumor formation is common after neuronal axotomy (73), we observed no sign of tumor formation at the site of injury up to 18 months after transplantation.…”
Section: Methodssupporting
confidence: 48%
“…Fibroblasts synthesize collagen and other ECM components that form the scaffold necessary for the migration and proliferation of other cell types involved in wound repair. Vimentin has been used routinely as a marker for dermal fibroblasts . Vimentin is one of the intermediate filaments expressed in cells of mesenchymal origin.…”
Section: Resultsmentioning
confidence: 99%
“…Regenerated epitheliums in the microsphere‐implanted group and untreated group showed thin and incompletely differentiated epithelial layers. Human vimentin, a specific marker of dermal fibroblasts,19 was detected at the regenerated dermis in the cell‐transplanted group [Figure 4(D)]. Tissue sections of the control groups trivially stained for human vimentin at 3 weeks after transplantation [Figures 5(C) and 6(C)], which showed crossreactivity of the antibodies used for immunohistochemistry against mouse vimentin.…”
Section: Resultsmentioning
confidence: 99%